Analysis of the influence of liquidity, capital adequacy ratio, and operational efficiency on profitability in the sustainability of Bank Mega Syariah - Salsabila, Sarah; Nasution, Anriza Witi; AK, Marlya Fatira; Rahmadani, Rahmadani; Seri, Ermyna (ARKA INSTITUTE, 2025)
This study aims to determine the effect of liquidity (NPF and FDR), Capital Adequacy Ratio (CAR) and operational efficiency (BOPO) on profitability (ROA) in the sustainability of Bank Mega Syariah. The sample in this study includes the financial statements of Bank Mega Syariah for the period 2010 to 2024 quarter I to IV with total of 60 periods. This study uses secondary data from OJK and Bank Mega Syariah publications. Data collection techniques with documentation studies. Data processing technique used a multiple linear regression test with a significant level of 5 percent (α = 5%). Based on the results of the study, it shows that NPF had an significant effect on the profitability of Bank Mega Syariah with a very low and inverse relationship, FDR had an significant effect on the profitability of Bank Mega Syariah with a low and inverse relationship, CAR had no significant effect on the profitability of Bank Mega Syariah with a very low relationship and inversely proportional, BOPO had an effect on the profitability of Bank Mega Syariah in a significant with a strong relationship and inversely proportional, NPF, FDR, CAR, and BOPO simultaneously had an significant effect on the profitability of Bank Mega Syariah.